2017
DOI: 10.1039/c6nj03801h
|View full text |Cite
|
Sign up to set email alerts
|

Efficient phenanthroimidazole-styryl-triphenylamine derivatives for blue OLEDs: a combined experimental and theoretical study

Abstract: Blue emitting devices based on 2-(4′-9H-carbazol-9-yl)-[1,1′-styryl]-4-yl-1-benzylpiperidine-1H-phenanthro[9,10-d]imidazole (Cz-BPIS) exhibits blue emission with CIE coordinates of (0.16, 0.09), current density of 1.91 cd/A, power efficiency of 1.63 lm/W and external quantum efficiency of 2.61%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“…The larger decrease of k nr in film than in solution may be because of restricted intermolecular rotation (RIR) which promotes strong aggregation induced emission enhancement (AIEE). 29…”
Section: Thermal and Electrochemical Propertiesmentioning
confidence: 99%
“…The larger decrease of k nr in film than in solution may be because of restricted intermolecular rotation (RIR) which promotes strong aggregation induced emission enhancement (AIEE). 29…”
Section: Thermal and Electrochemical Propertiesmentioning
confidence: 99%
“…S3, ESI †). [53][54][55][56][57][58][59][60] The effective spin-orbit coupling (SOC: S 1 H ˆSOT 5 ) of S 1 with the T 3 state also leads to enhanced EUE. 61 The calculated SOC of S 1 with T 3 follows the order of TPA-2SPPITPA (0.52 cm À1 ) 4 TPA-2SPPITPA (0.30 cm À1 ).…”
Section: Hlct Emitters With a Hot Exciton Modelmentioning
confidence: 99%
“…Up to now various conjugated systems, including pyrene, fluorene, anthracene, and phenanthroimidazole materials have been synthesized and used in OLED devices. Among the above‐mentioned materials, phenanthroimidazole is a deep‐blue emitting chromophore, has attracted remarkable attention because of the simple synthesis procedure, high fluorescence quantum yield, excellent thermal stability, and potential bipolar properties . For example, Ma et al.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain deep‐blue emitters, it has been suggested that by changing the molecular connectivity with the alkyl or alkene spacer and changing the linkage position from para to ortho or meta, the extent of conjugation could be well confined, However, there are few research groups applying this strategy for producing blue shift emission (blue emission) and high device performance simultaneously …”
Section: Introductionmentioning
confidence: 99%